Hypsibius vaskelae, a new species of Tardigrada (Eutardigrada, Hypsibiidae) from Russia - Tumanov, Denis V. (Zootaxa, 2018)
Hypsibius vaskelae sp. nov. (Tardigrada, Eutardigrada, Hypsibiidae) is described from a freshwater sample collected in the vicinity of Saint-Petersburg. The new species has wrinkled cuticle, bucco-pharyngeal apparatus with two elongate macroplacoids and septulum, and cuticular bars between the bases of inner and outer claw and near the base of the inner claw on legs I–IV. Hypsibius vaskelae sp. nov. is most similar to Hypsibius marcelli Pilato, 1990 and H. septulatus Pilato, Binda, Napolitano & Moncada, 2004, but differs from both in having wrinkled dorsal cuticle, thinner claws, and presence of lunules on the claws of all legs.